Role of gut microbes in acute lung injury/acute respiratory distress syndrome - Zixuan Ren; Zhihuan Zheng; Xiujing Feng (Gut Microbes)
Acute lung injury (ALI) is an acute, diffuse inflammatory lung condition triggered by factors of severe infections, trauma, shock, burns, ischemia-reperfusion, and mechanical ventilation. It is primarily characterized by refractory hypoxemia and respiratory distress. The more severe form, acute respiratory distress syndrome (ARDS), can progress to multi-organ failure and has a high mortality rate. Despite extensive research, the exact pathogenesis of ALI and ARDS remains complex and not fully understood. Recent advancements in studying the gut microecology of patients have revealed the critical role that gut microbes play in ALI/ARDS onset and progression. While the exact mechanisms are still under investigation, evidence increasingly points to the influence of gut microbes and their metabolites on ALI/ARDS. This review aims to summarize the role of gut microbes and their metabolites in ALI/ARDS caused by various triggers. Moreover, it explores potential mechanisms and discusses how gut microbe-targeting interventions might offer new clinical strategies for the treatment of ALI/ARDS.